The Correlation of Mothersâ€™ Satisfaction on Antenatal Care Service by Midwife and Motivation to Do Antenatal Care - Laily Prima Monica; Maria Ulfa (Journal of Ners and Midwifery, 2021)
The problem of maternal mortality and morbidity in Indonesia is still become a big problem. In fact, the maternal mortality rate in Indonesia is still the highest in Asean. The factors above are the direct causes of maternal mortality. The causes of this death can be minimized by antenatal care which monitors the condition of the mother's pregnancy regularly to predict the risks that may arise so that preventive measures can be taken. The design used correlational research with a cross-sectional approach. The population in this research was all pregnant women aged 20-35 years who did antenatal care at Polindes Jatinom Kecamatan Kanigoro Kabupaten Blitar as many as 12 pregnant women. The sampling technique used accidental sampling. The sample was some of the pregnant women aged 20-35 years who did antenatal care at the time of the research as many as 12 pregnant women. Results: The result showed 67% was in the category of very satisfied and 75% of pregnant women had high motivation towards antenatal care. There was a correlation between the satisfaction of pregnant women on antenatal care services by midwife andÂ  motivation to do antenatal care proven by the results of the Spearman Rank statistical test which showed the value of sig = 0,000. Midwives are expected to maintain and keep the quality of service, especially in providing antenatal care to pregnant women so that the needs of mothers during antenatal care are always satisfied.